Anomalous Propagation of Radio Waves from Distant ILS Localizers Due to Ionospheric Sporadic‐E - J. Sakai; S. Saito; K. Hosokawa; I. Tomizawa (Space Weather)
Abstract The ionospheric sporadic‐E (Es) layer occasionally causes anomalous propagation (AP) of VHF radio waves to distant locations. This effect, EsAP, may cause interference to VHF radio operation above 100 MHz. Recent study showed that VHF air navigation signals from distant stations are frequently observed when Es occurs. The observed frequencies includes channels of VHF omnidirectional radio range (VOR) and instrument landing system localizer (ILS LOC). The study showed that EsAP signals can be very strong and frequently exceeded the allowable interference limit of navigation receivers. In this paper, we focus on EsAP on ILS LOC channels using the data obtained in the previous study. A series of extremely strong signals was observed on an ILS LOC frequency at Kure, Japan, on 15 May 2014 when an ionosphere sounder observed high‐density Es. The source of the signal was identified as an ILS LOC‐type direction aid (LDA) at Hualien, Taiwan. During the same period, several EsAP signals were observed on other ILS LOC channels, but their strengths were less significant. Analysis showed the causes of the strong signal from Hualien LDA: (1) the center of the narrow radio beam passed through the region very close to the receiver site; (2) the elevation angle of the propagation path was very close to that of the actual beam center. Statistics showed that there were several outstanding EsAP events of which source was Hualien LDA. This study suggests that if similar conditions exist, radio interference to ILS LOC receiver can happen on any ILS LOC channels.